2018
DOI: 10.1111/rec.12904
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of passive restoration on density and diversity of regenerating tree species in mixed Dipterocarp forests of Nepal

Abstract: In many developing countries, the only affordable approach to recover ecosystem structure and function is through passive restoration. We conducted a 3 year study of passive restoration in mixed Dipterocarp forests dominated by Shorea robusta to examine the effectiveness of exclusion (fencing and fire suppression) on diversity, density, and richness of regenerating tree seedlings and saplings. We analyzed excluded and disturbed paired sites. We observed exclusion was effective in increasing seedling richness a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 76 publications
(90 reference statements)
1
1
0
Order By: Relevance
“…Calleja et al, (2019) reported that livestock grazing had very low impact on shrub encroachment as it was observed that the cattle prefer herbaceous plants to woody species. Similarly, consistent with the results of Sapkota and Stahl (2018), invasive species richness was found higher at low grazed area despite having no significant difference in species diversity with high grazed area (Fig. 4 and Fig.…”
Section: Grazing Intensity Vegetation Composition and Diversitysupporting
confidence: 89%
“…Calleja et al, (2019) reported that livestock grazing had very low impact on shrub encroachment as it was observed that the cattle prefer herbaceous plants to woody species. Similarly, consistent with the results of Sapkota and Stahl (2018), invasive species richness was found higher at low grazed area despite having no significant difference in species diversity with high grazed area (Fig. 4 and Fig.…”
Section: Grazing Intensity Vegetation Composition and Diversitysupporting
confidence: 89%
“…Failure of natural regeneration of planted species other than bamboo in the trial area likely reflects dispersal and soil propagule bank limitations and the lack of safe sites in shallow soils on steep and dissected slopes, with long histories of anthropogenic disturbances (Adnan & Holscher 2011; Semwal et al 2013). A 20‐year period of restoration may be too short to catalyze passive restoration of economic species in temperate Himalaya, unlike tropical Himalayan foothills (Sapkota & Stahl 2019) and other eco‐regions (Meli et al 2017 a ). Active restoration is expensive, but may be a necessity for securing the participation of people desiring early material benefits and high income (Nguyen et al 2015; Holmes et al 2017; Wang et al 2019).…”
Section: Discussionmentioning
confidence: 99%